ANALYSIS OF THE DIFFERENCE IN AVERAGE ABNORMAL RETURNS OF BIG BANKS STOCKS BEFORE AND AFTER THE FEDERAL RESERVE'S INTEREST RATE CHANGES (STUDY OF EVENTS IN 2022-2024) - Frederik Franston; Luke Suciyati Amna (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The banking sector as one of the sectors that dominate the Indonesian stock market is very sensitive to changes in interest rates so this move can affect profitability so investors will make decisions on this information. This study aims to analyze the impact of the Fed's interest rate changes on the Average Abnormal Return (AAR) of Big 4 Banks stocks in Indonesia during the 2022-2024 period. The banking sector is very sensitive to changes in interest rates so it can affect profitability so investors will make decisions on this information. The event study method was used with a pre-event window (t-5 to t-1), event day (t0), and post-event window (t+1 to t+5). The data used came from newyorkfed.com, investing.com, and idx.co.id. The results showed that there was no significant difference in AAR before and after the change in interest rates, both the increase during 2022-2023 and the decrease in September 2024, as evidenced by the significance values of the Paired Sample T-Test of 0.130 and 0.057 (> 0.05, respectively).